Service quality gap in hospitality industry: a comparison between various homestay in southern Malaysia / Noreen Noor Abd Aziz, Zurina Omar and Nur Adilah Saud - Abd Aziz, Noreen Noor; Omar, Zurina; Saud, Nur Adilah (Research Management Institute (RMI), 2010)
Homestay programme is one of the tourism product that being promote by the government. Homestay is where you get to stay with a selected family from different background and culture as your foster family for duration of time. In addition, you will be experienced the way of their daily life. There are some limitations and problems identified that can affect the homestay industry to go further expanding their market.This study focus on selected homestay in Southern Malaysia including Johor, Negeri Sembilan and Melaka. The aim of this study are to determine which factor of service quality dimension that has significant impact to homestay industry, to identify consumer's expectation and perception of each service quality dimensions and to identify gap between expectations and perceptions of service quality dimensions. This study utilizes five dimensions of service quality model to measure gap between customer's expectation and perception in homestay industry. The findings showed that the main factor of service quality dimension that have significant impact to the homestay industry are assurance for consumer expectation and reliability for consumer perception. For overall result indicated that the biggest positive gap (mean) was reliability and negative gap (mean) was tangible.